Evaluating the impact of shift work length and time of day on musculoskeletal disorders among nursing assistants in long-term care - Ryan L. Bellacov; Kermit G. Davis; Chunhui He (Human Factors in Healthcare)
AIM: This study aimed to investigate differences in activity and body movements for the different 8-hour shifts and extended 12-hour shifts at a long-term healthcare facility. The secondary aim will focus on determining the impact of shift work time of day on musculoskeletal injuries causing days off. Background: Nursing assistants have heavy physical workloads, which results in high turnover and musculoskeletal pain. Methods: The research team observed 240 shifts for 54 nursing assistants in five long-term healthcare facilities. The researchers completed direct observations of posture through the utilization of an ergonomic evaluation tool using the Rapid Entire Body Assessment using a random sampling (equivalent of 12 times per hour). An activity monitor continuously captured the time spent sitting, standing, and walking, along with the associated energy expenditure while working. Results: The most significant results were in physical activity, with an 8-hour day percent of total time walking being double the amount at 48.4% compared to night shifts at 23.1% (total steps per hour: 1704 compared to 763, respectively). REBA scores for the upper body on the day shift are more ergonomically challenging (risk rating: 7 to 5, respectively). The 12-hour shifts negatively impact on the lower back and shoulder, causing injuries in long-term care. Conclusion: Overall, an 8-hour day had the most impact on energy expenditure. In addition, 8-hour shifts had a higher incidence of lower back pain, resulting in the most frequent loss of work. The incidence of loss of workdays affects employee well-being, productivity, and medical associated costs. Nearly 20% of the nurse assistants' observations had poor posture with medium to high risk. Implications: Healthcare managers could help the physical strain that nursing assistants endure by targeting footwear, poor posture, and fatigue. While the higher workload in this study did not equate to higher musculoskeletal pain, the complexity of the normal work tasks likely resulted in complex demands on the nursing assistants.